EFEKTIVITAS KULIT BUAH NAGA SEBAGAI FEED ADDITIVE TERHADAP PROFIL SALURAN PENCERNAAN AYAM BROILER DENGAN CEKAMAN PANAS - Nur Widodo; Himatul Khasanah; Roni Yulianto; Desy Cahya Widianingrum; Herlinda Putri Utami (Journal of Innovation Research and Knowledge, 2025)
Heat stress is one of the indicators that can reduce broiler productivity. Heat stress can interfere with the health of the digestive tract. Dragon fruit peel is a plant that has antioxidant and antimicrobial activities that can reduce the effects of heat stress on broiler chickens. This study aims to determine the effect of dragon fruit peel flour (TKBN) in the diet on the digestive tract profile of broiler chickens raised at different temperatures. This study used a completely randomized design with 4 treatments and each treatment consisted of 5 replicates. The treatments in this study consisted of P1 (0% TKBN + temperature 23-25oC), P2 (1.5% TKBN + temperature 23-25oC), P3 (0% TKBN + temperature 33-35oC) and P4 (1.5% TKBN + 33-35oC). The variables observed in this study consisted of the length and weight of the digestive organs (proventriculus, gizzard, small intestine, cecum and large intestine) as well as the histomorphology of the small intestine (villus length, villus width, krypta depth, and the ratio of villus length and krypta depth). The data obtained were processed by analysis of variance (ANOVA) and if the effect was significant, Duncan Multiple Range Test (DMRT) was conducted. The results showed that different levels of dragon fruit peel flour and rearing temperature had a significant effect (P<0.05) on the length of the villi, the width of the villi and the depth of the crypta, but no significant effect (P>0.05) on the length and weight of the digestive organs and the ratio of villi and crypta. The average increase in villus length, villus width and crypta depth was shown by treatment P2 (1.5% TKBN + temperature 23-25oC).